2021
DOI: 10.1111/ans.17221
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer databases and registries in Australia: what data is available?

Abstract: Background There are multiple data sources relating to colorectal cancer (CRC) nationwide. Prospective clinical cancer databases, population‐based registries and linked administrative data are powerful tools in clinical outcomes research and provide real‐world perspective on cancer treatments. This study aims to review the different Australian data sources for CRC from the perspective of conducting comparative research studies using a PICO (patient, intervention, comparison, outcome) framework. Methods Data di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Five articles were identified that reviewed CIR. [7][8][9][10][11] Strengths included (1) epidemiological data from CIR captured population data and is more generalisable compared to COR, 10 (2) larger sample size compared to COR, 11 and (3) its utility lies in evaluation of productivity of national health screens and treatment services in improving cancer incidence. 9 Logistically, CIR falls short in database accuracy, reporting large amounts of missing data requiring follow up and outdated cancer diagnosis criteria, resulting in many missing notifications from hospitals.…”
Section: Cancer Incidence Registry(cir) Evaluationmentioning
confidence: 99%
“…Five articles were identified that reviewed CIR. [7][8][9][10][11] Strengths included (1) epidemiological data from CIR captured population data and is more generalisable compared to COR, 10 (2) larger sample size compared to COR, 11 and (3) its utility lies in evaluation of productivity of national health screens and treatment services in improving cancer incidence. 9 Logistically, CIR falls short in database accuracy, reporting large amounts of missing data requiring follow up and outdated cancer diagnosis criteria, resulting in many missing notifications from hospitals.…”
Section: Cancer Incidence Registry(cir) Evaluationmentioning
confidence: 99%
“…4 They can, however, provide further information when information from administrative data sets is linked to the minimum dataset collected through a CQR as exemplified by the article on colorectal cancer databases in this issue of the Journal. 5 There are many local examples of CQRs that have led to improvement in patient care as a result of their primary reporting function. The Australian Orthopaedic Association National Joint Replacement Registry identified a higher-than-expected reoperation rate for a hip resurfacing prosthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Administrative datasets have been shown to lack sensitivity and have high false positive rates when interrogated about surgical complications and compared to a purposefully collected registry dataset 4 . They can, however, provide further information when information from administrative data sets is linked to the minimum dataset collected through a CQR as exemplified by the article on colorectal cancer databases in this issue of the Journal 5 …”
Section: Introductionmentioning
confidence: 99%
“…12 One of the challenges of investigating the relationship between cancer stage at diagnosis and socioeconomic disadvantage on a population level is the relative lack of detailed staging information in population-based cancer registries, which could explain why findings are inconsistent among different data sources. 13,14 Rather than information derived from individual patients, arealevel indices are frequently used to capture relative socioeconomic advantages or disadvantages. Within a certain geographic area, these indices are based on an aggregate of various measures, such as average household income, rate of unemployment, the highest level of education and number of unskilled workers.…”
Section: Introductionmentioning
confidence: 99%
“…found that stage at diagnosis did not fully account for differences in survival by socioeconomic status 12 . One of the challenges of investigating the relationship between cancer stage at diagnosis and socioeconomic disadvantage on a population level is the relative lack of detailed staging information in population‐based cancer registries, which could explain why findings are inconsistent among different data sources 13,14 …”
Section: Introductionmentioning
confidence: 99%